2018
DOI: 10.1111/aor.13103
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of ECG‐Synchronized Pulsatile Flow Using the i‐cor Diagonal Pump in Neonatal and Pediatric ECLS Systems

Abstract: The objective was to assess the i-cor electrocardiogram-synchronized diagonal pump in terms of hemodynamic energy properties for off-label use in neonatal and pediatric extracorporeal life support (ECLS) circuits. The neonatal circuit consisted of an i-cor pump and console, a Medos Hilite 800 LT oxygenator, an 8Fr arterial cannula, a 10Fr venous cannula, 91 cm of 0.6-cm ID arterial tubing, and 91 cm of 0.6-cm ID venous tubing. The pediatric circuit was identical except it included a 12Fr arterial cannula, a 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Our results once again showed that the i‐cor diagonal pump can generate non‐pulsatile and ECG‐synchronized pulsatile flow in our simulated pediatric and adult ECLS circuits . The i‐cor diagonal pump can generate pulsatile flow by changing the rotational speed.…”
Section: Discussionsupporting
confidence: 64%
“…Our results once again showed that the i‐cor diagonal pump can generate non‐pulsatile and ECG‐synchronized pulsatile flow in our simulated pediatric and adult ECLS circuits . The i‐cor diagonal pump can generate pulsatile flow by changing the rotational speed.…”
Section: Discussionsupporting
confidence: 64%
“…We intentionally did not include the results from this particular diagonal pump in the materials and methods section of this manuscript, as it has not been approved by the FDA for clinical practice in the United States. The i‐Cor DP3 diagonal pump is also capable of providing pulsatile flow in addition to conventional non‐pulsatile flow . In addition, the i‐Cor pump is capable of providing ECG‐synchronized pulsatile flow by syncing the pulses of the pump with the patient’s native heartbeat.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pulsatile flow during acute or chronic mechanical circulatory support for pediatric or adult patients is one of the major research areas at the Penn State Hershey Pediatric Cardiovascular Research Center. [16][17][18][19] The predecessor of the PediMag centrifugal pump was the Levitronix PediVAS system, which is capable of generating pulsatile flow and has been tested in an experimental setting at our research center. This pulsatile module was intended for experimental use only and has not been approved by the Food and Drug Administration (FDA) for use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morgan Moroi et al of the Penn State Health Children's Hospital, Hershey, PA, USA, assessed the i‐cor electrocardiogram‐synchronized diagonal pump in terms of hemodynamic energy properties for off‐label use in neonatal and pediatric extracorporeal life support (ECLS) circuits. Pulsatile flow generated significantly higher total hemodynamic energy (THE) levels than nonpulsatile flow.…”
Section: Cardiac Support and Blood Pumpsmentioning
confidence: 99%